Motivating hotel employees in Poland - Wszendybył-Skulska, Ewa (Motywowanie pracowników hoteli w Polsce, 2019)
Research into the effective ways of motivating employees occupies an important place in the literature of the subject. For many years the research on motivation to work has mainly been focused on the payment. Nowadays, more and more attention is given to using the non-financial tools in the motivation process. Today, motivating employees to work in the hotel industry includes a number of personalized incentive instruments. The purpose of the study is to check what types of motivators are most often used by hotel managers in Poland to motivate line employees. The research has shown that hoteliers in Poland most often use such motivators as work atmosphere, interpersonal relations, showing respect, rewards and bonuses, salary, and flexible working hours, while the least used are those based on digital solutions that can support the daily work of employees, communication with colleagues and superiors and their development
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 10, s. 235-247